(untitled) - Naborov, Vladimir Vladimirovich (New York, NY, 1996)
Vladimir Nabokov came to the United States and went on to an even more brilliant one in English--earning a place as one of the greatest writers of his adopted home. Between 1941 and 1974 he published the autobiography and eight novels now collected by The Library of America in an authoritative three-volume set. "The Real Life of Sebastian Knight" is a tantalizing literary mystery in which a writer's half brother searches to unravel the enigma of the famous novelist's life
Keywords: American literature,American fiction,Naborov, Vladimir Vladimirovich, 1899 - 1977; 20th century,20th century